PENTINGNYA DUE AUDIT CAREDALAM KUALITAS AUDIT SEKTOR PRIVAT DAN SEKTOR PUBLIK - T. Tumirin (InFestasi, 2006)
The concept of due audit care divided into two part the fistcalls for establishment of the idea of a prudent practitioner, the secondfor an indication of the care with which he will perform under varyingcondition. The due audit care as a possible way indicating theresponsibility the profession for detecting irregularities. Thecharacteristics of irregularities are materiality, intent, relationship tointernal control, influence on financial statement, and responsibility.Audit quality defined as the probability that the auditor will bothdiscover and report a breach in the clients’ accounting system. Thesedue audit care guarantee quality of audit in private sector or publicsector